2010
DOI: 10.20450/mjcce.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-ESI-MSn identification of phenolic compounds in cultivated strawberries from Macedonia

Abstract: Strawberry fruits contain phenolic compounds that exhibit antioxidant, anticancer, antiatherosclerotic, antinflammatory and anti-neurodegenerative properties. High-performance liquid chromatography (HPLC) coupled to electrospray ionization mass spectrometric (ESI-MS) detection in the positive and negative ion mode has been used to identify the phenolic compounds in extracts from sixteen different strawberry cultivar fruits from Republic of Macedonia. Photodiode-array detection (DAD) has been used for screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 35 publications
13
85
1
Order By: Relevance
“…Several peaks were tentatively assigned as kaempferol derivatives based on their ESI‐MS/MS spectra, such as ( Co 8) with [M−H] − ion at m / z 533.1300, which is consistent with the report on kaempferol‐3‐ O ‐malonylglucoside, with fragment ions corresponding to kaempferol hexoside ( m / z 447) and kaempferol ion ( m / z 285) after loss of the malonyl moiety (–86 amu) and hexose moiety (–162 amu), respectively (Kajdžanoska, Gjamovski, & Stefova, ). Furthermore, peak ( Co 18) was associated with [M−H] − at m / z 489.1037 and a main fragment at m / z 285, after loss of acetyl hexose (–204 amu), and was identified as kaempferol‐3‐ O ‐acetyl hexoside.…”
Section: Resultssupporting
confidence: 85%
“…Several peaks were tentatively assigned as kaempferol derivatives based on their ESI‐MS/MS spectra, such as ( Co 8) with [M−H] − ion at m / z 533.1300, which is consistent with the report on kaempferol‐3‐ O ‐malonylglucoside, with fragment ions corresponding to kaempferol hexoside ( m / z 447) and kaempferol ion ( m / z 285) after loss of the malonyl moiety (–86 amu) and hexose moiety (–162 amu), respectively (Kajdžanoska, Gjamovski, & Stefova, ). Furthermore, peak ( Co 18) was associated with [M−H] − at m / z 489.1037 and a main fragment at m / z 285, after loss of acetyl hexose (–204 amu), and was identified as kaempferol‐3‐ O ‐acetyl hexoside.…”
Section: Resultssupporting
confidence: 85%
“…Additional fragments at m/z 283, 269 and 179 were also detected. Compounds 14 , 20 , 22 and 29 were identified as a ferulic acid 5‐ O ‐hexoside derivative, neohesperidin, kaempferol 3‐O‐hexoside and diosmetin 7‐ O ‐dihexoside, respectively (Kajdžanoska et al, ; Lin & Harnly, ). Compound 14 presented an [M − H] − ion at m/z 449, which was further fragmented to m/z 431, 287 and 269, consistent with the published literature.…”
Section: Resultsmentioning
confidence: 99%
“…1 H, APT, COSY and HMBC NMR spectral data for compound 3 in are summarized in Table 3. On the basis of the obtained data, and by comparing with the reported literature (Harborne, 1994;Kajdžanoska et al, 2010;Nawwar et al, 1984), compound 3 was identified as kampferol-3-O--D-glucuronide.…”
Section: Compoundmentioning
confidence: 54%